Five to 25 Gb/s continuous time linear equaliser with transversal architecture. Issue 25 (1st December 2017) - Zhang, H.; Monaco, E.; Bassi, M.; Mazzanti, A.
Abstract : Transceivers for backplane serial links operating up to 25 Gb/s demand flexible equalisers with high accuracy in matching the channel response. A continuous time linear equaliser (CTLE) with a transversal architecture features variable DC gain and two zeros that can be tuned independently. The transversal architecture yields a paraboloid mean‐square‐error surface, allowing optimal adaptation through gradient descent algorithms. The CTLE was realised in a 28 nm CMOS technology and measurements are presented at data rate from 5 to 25 Gb/s across 20 dB‐loss channels. Core power dissipation is 17 mW from 1 V supply and horizontal eye opening at BER 10 −12 is equal or larger than 50%, comparing favourably against previously reported equalisers targeting similar data‐rate and channel loss.